Pobot in dogovor o izravnavi - Šlamberger, Miha (Podjetje in delo, 2017)
Various measures and instruments are used in business practice, especially in relations between financial institutions, for exposure mitigation. These instruments need to survive any insolvency procedures against any of the parties, especially in cross-border relations. Such an instrument is close-out netting. In the following article I am comparing the close-out netting instrument, typical for financial collateral agreements, and set-off, as a standard way of closing the exposure. The advantages of close-out netting are seen in insolvency procedures against the other party.
Keywords: close-out netting; financial collateral; finančna zavarovanja; insolvency; insolventnost; neto izravnava; pobot; set-off